Ginástica e educação física no instituto Benjamin Constant de 1930 a 1979: entre a conformação e a formação humanística da pessoa cega - Moises, Ronaldo Rodrigues (2019)
This research investigates the development of Gymnastics with its subsequent unfolding in the discipline Physical Education at the Benjamin Constant Institute (IBC) in the temporal cutout from 1930 to 1979. The IBC was originally created during the monarchic period in 1854 by Don Pedro II, being to the present day the greatest formative reference and care for blind people or visual impairment in all of Latin America. The general objective of this thesis is to analyze the contribution of Gymnastics and Physical Education within the Benjamin Constant Institute in the humanistic formation of blind students between 1930 and 1979, establishing a dialectical correlation with the Brazilian development process observed during the period. The hypothesis defended is that Gymnastics/Physical Education, despite its positivist/militaristic origin for the purpose of forming a strong, obedient, sound and eugenic nation, was treated in the Institute as a counter-hegemonic resource of humanist basis, being a precursor to a process that would later culminate in the social inclusion of blind students. The theoretical framework adopted is linked to historical-dialectical materialism. We used for the investigation of bibliographic and documentary research through primary historical sources as well as synthesis of researchers in the areas of History of Education, History of Physical Education and History of Special Education. It was concluded that Physical Education followed the development of varied ideas and the process of development of national historical time, presenting in the IBC proposals with the biases, playful, eugenic, splicitive, sportsmanship and pedagogical rethinking, however, linked to the capitalist mode of production and its hegemonic ideology presenting, at different times, flashes of contribution of humanistic formation, counter-hegemonic and socialization to blind students.